Buprenorphine & methadone dosing strategies to reduce risk of relapse in the treatment of opioid use disorder. (1st October 2022) - Rudolph, Kara E.; Williams, Nicholas T.; Goodwin, Alicia T. Singham; Shulman, Matisyahu; Fishman, Marc; Díaz, Iván; Luo, Sean; Rotrosen, John; Nunes, Edward V.
Abstract: Background: Although there is consensus that having a "high-enough" dose of buprenorphine (BUP-NX) or methadone is important for reducing relapse to opioid use, there is debate about what this dose is and how it should be attained. We estimated the extent to which different dosing strategies would affect risk of relapse over 12 weeks of treatment, separately for BUP-NX and methadone. Methods: This was a secondary analysis of three comparative effectiveness trials. We examined four dosing strategies: 1) increasing dose in response to participant-specific opioid use, 2) increasing dose weekly until some minimum dose (16 mg BUP, 100 mg methadone) was reached, 3) increasing dose weekly until some minimum and increasing dose in response to opioid use thereafter (referred to as the "hybrid strategy"), and 4) keeping dose constant after the first 2 weeks of treatment. We used a longitudinal sequentially doubly robust estimator to estimate contrasts between dosing strategies on risk of relapse. Results: For BUP-NX, increasing dose following the hybrid strategy resulted in the lowest risk of relapse. For methadone, holding dose constant resulted in greatest risk of relapse; the other three strategies performed similarly. For example, the hybrid strategy reduced week 12 relapse risk by 13 % (RR: 0.87, 95 %CI: 0.83–0.95) and by 20 % (RR: 0.80, 95 %CI: 0.71–0.90) for BUP-NX and methadone respectively, as compared to holding dose constant. Conclusions: Doses should be targeted toward minimum thresholds and, in the case of BUP-NX, raised when patients continue to use opioids. Highlights: Among those initiating buprenorphine or methadone for OUD, what dosing strategy would result in the lowest risk of relapse? Doses should be targeted toward minimum thresholds and, for buprenorphine, raised when patients continue to use opioids. For buprenorphine, increasing to at least 16 mg and then increasing in response to use resulted in lowest risk of relapse. For methadone, the three dose increase strategies performed similarly and lowered relapse risk vs. holding dose constant.